Treatment of Anisometropic Amblyopia in Children with Refractive Correction (2006)
OBJECTIVE: To evaluate the effectiveness of refractive correction alone for the treatment of untreated anisometropic amblyopia in children 3 to <7 years old. DESIGN: Prospective, multicenter, noncomparative intervention. PARTICIPANTS: 84 children 3 to <7 years old with untreated anisometropic amblyopia ranging from 20/40 to 20/250. METHODS: Optimal refractive correction was provided and visual acuity was measured with the new spectacle correction at baseline, and at 5-week intervals until visual acuity stabilized or amblyopia resolved. MAIN OUTCOME MEASURES: Maximum improvement in best-corrected visual acuity in the amblyopic eye and proportion of children whose amblyopia resolved (interocular difference of 1 line or less) with refractive correction alone. RESULTS: Amblyopia improved with optical correction by 2 or more lines in 77% of the patients and resolved in 27%. Improvement took up to 30 weeks for stabilization criteria to be met. After stabilization, additional improvement occurred with spectacles alone in 21 of 34 patients followed in a control group of a subsequent randomized trial, with amblyopia resolving in 6. Treatment outcome was not related to age, but was related to better baseline visual acuity and lesser amounts of anisometropia. CONCLUSION: Refractive correction alone improves visual acuity in many cases and results in resolution of amblyopia in at least one third of 3 to <7-year-old children with untreated anisometropic amblyopia. While most cases of resolution occur with moderate (20/40 to 20/100) amblyopia, the average 3-line improvement in visual acuity resulting from treatment with spectacles may lessen the burden of subsequent amblyopia therapy for those with denser levels of amblyopia. PRECIS: Refractive correction alone improves visual acuity in many cases and results in resolution of amblyopia in at least one third of children 3 to <7 years old with untreated anisometropic amblyopia.